THE IMPACT OF E-COMMERCE IMPLEMENTATION ON THE PERFORMANCE OF MICRO AND SMALL INDUSTRIES IN INDONESIA - Silaban, Soeripto; Kusnadi, Nunung; Feryanto, Feryanto (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2024)
The micro and small industries play an important role in the growth of the national economy, as evidenced by the increasing number of micro and small business units every year and their contribution to the Gross Domestic Product (GDP). However, the COVID-19 pandemic has decreased revenue for micro and small industry players, forcing them to make efficiency measures in their business. To overcome this difficult situation, implementing e-commerce in micro and small industries is considered an important marketing strategy to maintain business continuity. In fact, only a few micro and small business actors apply e-commerce. This study aims to analyze the factors that influence the implementation of e-commerce in micro and small industries, as well as the impact of e-commerce implementation on the performance of micro and small businesses in Indonesia. The data used in this study were secondary data from the 2019 survey of micro and small industries conducted by the Central Statistics Agency (BPS), and the respondents were categorized into two groups: micro and small industries (SMI) that implement e-commerce and those that do not. The data was analyzed using propensity score matching. The study results showed that the implementation of e-commerce has a positive and significant impact on the performance of micro and small industries, namely an increase in employees, revenue, and business profit.